A degradable polymer repair material and preparation method thereof

Through the combination preparation of polyanhydride and other materials, the problem of insufficient hardness and difficulty in degradation of chest wall repair materials is solved, the biocompatibility and mechanical strength of polymer repair materials is achieved, the repair of chest wall defects and bone regeneration is promoted, and the body is avoided Complications of foreign body retention.

CN116966337BActive Publication Date: 2024-12-13THE FOURTH HOSPITAL OF HEBEI MEDICAL UNIVERSITY (HEBEI CANCER HOSPITAL)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310888222.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2024-12-13
Estimated Expiration
2043-07-19

AI Technical Summary

Technical Problem

The existing chest wall repair materials have problems such as insufficient hardness, difficulty in degradation and tissue reactions during chest wall resection surgery, making it difficult to effectively repair large-area chest wall defects, resulting in respiratory and circulation disorders.

Method used

A degradable polymer is prepared by combining polyanhydride, calcium phosphate, lactic acid, glycolic acid, polyethylene glycol, bioactive liquid and antibacterial agent in a specific proportion by stirring, freeze-drying, melt copolymerization, spinning and soaking. Repair the material to form a porous material with mechanical strength, cytocompatibility and antibacterial properties.

Benefits of technology

This material can effectively promote the repair of chest wall defects, enhance bone regeneration ability, provide good biocompatibility and mechanical properties, degrade into non-toxic small molecule substances, avoid the retention of foreign objects in the body, and ensure the recovery and support function of the chest.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GHA0000008203440000101
    Figure GHA0000008203440000101
Patent Text Reader

Abstract

The present invention provides a degradable polymer repair material and a preparation method thereof, and relates to the technical field of medical biomaterials. A degradable polymer repair material, by weight, comprises: 1-10 parts of polyanhydride, 0.5-2.5 parts of calcium phosphate, 1-10 parts of lactic acid, 0.1-1 parts of polyethylene glycol, 1-10 parts of glycolic acid, 1-5 parts of biologically active liquid and 1-5 parts of antibacterial agent. The degradable polymer repair material of the present invention has special biological activity, good biocompatibility and biosafety, and also has excellent mechanical strength, chemical stability, and is biodegradable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical biomaterials, and in particular to a degradable polymer repair material and a preparation method thereof. Background Art

[0002] The regeneration and repair of damaged human tissues has always been a difficult problem faced in clinical practice. In recent years, with the development of cell biology and tissue engineering technology, biomaterial composite patches are patches with scaffold adjustability formed by natural degradable biomacromolecules and degradable polymer woven materials. As a biomaterial scaffold, it can promote the repair of tissue defects through spatial induction and tissue replacement. Since it does not contain or even contains very little components that cause host immune rejection reactions, it has good tissue compatibility and can be widely used in the repair of defective tissues in various clinical fields, and has achieved good application prospects.

[0003] Biomaterial composite patches are relatively mature in the repair of thoracic surgery, especially for the treatment of combined infection. In chest wall resection surgery, when the chest wall defect is too large, a substitute is needed to rebuild the chest wall to restore the support strength and elasticity of the thorax, otherwise it will cause abnormal breathing of the chest wall after surgery, causing respiratory and circulatory disorders.

[0004] At present, there are many materials used in the clinic to repair chest wall defects, including autologous tissue, allogeneic tissue, artificial materials, etc. Autologous tissue is considered to be the most suitable repair material for human physiology, including fascia lata, muscle flap, greater omentum, etc., but its material is limited, which will increase trauma, and its hardness is not enough; allogeneic tissue is mostly ribs preserved after thoracotomy, or heterogeneous materials such as allogeneic sternum, dura mater and pericardium, which are insufficient in source and inconvenient to use; artificial materials include hard materials and soft materials, but they are not easily degraded, resulting in greater tissue reaction. Therefore, it is particularly important to research and develop a degradable repair material. Summary of the invention

[0005] The purpose of the present invention is to provide a degradable polymer repair material which has special biological activity, good biocompatibility and biosafety, as well as excellent mechanical strength, chemical stability and biodegradability.

[0006] Another object of the present invention is to provide a method for preparing a degradable polymer repair material, which is used to prepare the above-mentioned degradable polymer repair material and make it have excellent performance.

[0007] The present invention solves the technical problem by adopting the following technical solutions.

[0008] The present invention provides a degradable polymer repair material, which comprises the following raw materials by weight: 1-10 parts of polyanhydride, 0.5-2.5 parts of calcium phosphate, 1-10 parts of lactic acid, 0.1-1 parts of polyethylene glycol, 1-10 parts of glycolic acid, 1-5 parts of biologically active liquid and 1-5 parts of antibacterial agent.

[0009] The present invention provides a method for preparing a degradable polymer repair material, comprising the following steps:

[0010] The polyethylene glycol is dissolved in water, and then calcium phosphate and polyanhydride are added, stirred, aged for 2-5 days, and freeze-dried to obtain a first polymer monomer; lactic acid and glycolic acid are melt-copolymerized to obtain a second polymer monomer; the first polymer monomer and the second polymer monomer are mixed and melted, an antibacterial agent is added, spun, cooled and shaped to obtain a prefabricated material, and the prefabricated material is immersed in a bioactive liquid, dried, and obtained a finished product.

[0011] The present invention has at least the following beneficial effects:

[0012] In the present invention, the polyanhydride has good fiber-forming properties and mechanical strength, and can form a porous first polymer monomer with a certain mechanical strength after cross-linking with calcium phosphate. It has cell compatibility, can enhance cell proliferation and adhesion, and can effectively promote the repair of chest wall defect tissue. The second polymer monomer is obtained after copolymerization of lactic acid and glycolic acid, which can enhance the ability of bone regeneration, and also has obvious antibacterial, bone conduction, bone induction and other properties, which can promote the recovery of the thorax. At the same time, its good relatively long-term mechanical properties in the human body can further improve the mechanical properties of the repair material. Polyethylene glycol has excellent gelation and degradability, good biocompatibility, non-toxicity and low immunogenicity. The first polymer monomer and the second polymer monomer are combined to make the material have very good softness, crystallinity and degradability. Assisted by antibacterial agents, the protective effect on wounds can be improved, and assisted by biologically active liquids, nutrients can be supplemented and cell reproduction can be promoted to further enhance the repair effect on chest wall defects and promote body recovery.

[0013] In the present invention, the repair material is degraded from high molecular weight and macromolecular substances into small molecular substances that do not harm the body through the action of hydrolysis and enzymolysis, and these small molecular degradation products usually exist in the body itself, such as amino acids, carbon dioxide, water, etc., and finally completely absorbed and excreted through the body's metabolism, without toxic side effects to the body, and can avoid the problem of related complications caused by the long-term retention of foreign matter in the body. The specific degradation process is: the surface of the degradable polymer material is adhered by microorganisms, and under the action of enzymes secreted by microorganisms, the polymer breaks into relatively small molecular fragments, and the microorganisms absorb or consume the fragments, and finally form water and carbon dioxide through metabolism. DETAILED DESCRIPTION

[0014] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0015] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other. The present invention will be described in detail below with reference to specific embodiments.

[0016] A degradable polymer repair material comprises the following raw materials by weight: 1-10 parts of polyanhydride, 0.5-2.5 parts of calcium phosphate, 1-10 parts of lactic acid, 0.1-1 parts of polyethylene glycol, 1-10 parts of glycolic acid, 1-5 parts of bioactive liquid and 1-5 parts of antibacterial agent.

[0017] Polyanhydride has good fiber-forming properties and mechanical strength. After cross-linking with calcium phosphate, it can form a porous scaffold with certain mechanical strength. At the same time, the scaffold is also cell-compatible, can enhance cell proliferation and adhesion, and can effectively promote the repair of chest wall defect tissue.

[0018] The high molecular polymer obtained by copolymerization of lactic acid and glycolic acid can enhance the ability of bone regeneration, and also has obvious antibacterial, bone conduction, bone induction and other properties, which can promote the recovery of the thorax. At the same time, its good relatively long-term mechanical properties in the human body can further improve the mechanical properties of the repair material.

[0019] Polyethylene glycol has excellent gelation and degradability, good biocompatibility, non-toxicity and low immunogenicity.

[0020] The combination of the first polymer monomer and the second polymer monomer can make the material have very good softness, crystallinity and degradability. With the addition of antibacterial agents, it can improve the protection of wounds, and with the addition of biologically active liquid, it can supplement nutrients and promote cell reproduction, so as to further enhance the repair effect on chest wall defects and promote body recovery.

[0021] In detail, the bioactive liquid includes collagen and epidermal growth factor, and the mass ratio of the two is 1:2-4.

[0022] Collagen itself is the skeleton of the extracellular matrix. Its triple helix structure and the fibers or networks formed by cross-linking play an anchoring and supporting role for cells and provide an appropriate microenvironment for the growth of cell proliferation. It can interact well with the matrix around the cells, showing a coordinated influence on each other, and become an integral part of the normal physiological function of cells and tissues. Collagen can be degraded by specific proteases, that is, biodegradable. Specifically, collagen is degraded by enzymes, breaking collagen peptide bonds, destroying its helical structure and completely hydrolyzing it into small molecular polypeptides or amino acids. Small molecules can enter the blood circulation system and be reused or metabolized and excreted by the body. Collagen has hemostatic properties, can promote platelet aggregation and plasma clots, and plays a hemostatic role by bonding and aggregating with platelets to form thrombi. Epidermal growth factor can promote the synthesis of DNA, RNA and hydroxyproline in the process of skin wound tissue repair, induce the reverse transformation of differentiated mature epidermal cells into epidermal stem cells, accelerate the formation of wound granulation tissue and the proliferation of epithelial cells, thereby shortening the healing time of the wound and improving the quality of wound repair. Collagen and epidermal growth factor can supplement nutrients for damage repair, promote cell reproduction, and thus accelerate trauma repair.

[0023] In detail, the antibacterial agent is a mixture of berberine and curcumin, and the mass ratio of the two is 1:1.5-1.8. The combination of berberine and curcumin has a significant antibacterial effect, can prevent bacterial infection at the chest wall defect, promote wound healing, and also has a certain analgesic effect, can reduce the body's discomfort, and improve the comfort during use.

[0024] A method for preparing a degradable polymer repair material comprises the following steps:

[0025] The polyethylene glycol is dissolved in water, and then calcium phosphate and polyanhydride are added, stirred, aged for 2-5 days, and freeze-dried to obtain a first polymer monomer; lactic acid and glycolic acid are melt-copolymerized to obtain a second polymer monomer; the first polymer monomer and the second polymer monomer are mixed and melted, an antibacterial agent is added, spun, cooled and shaped to obtain a prefabricated material, and the prefabricated material is immersed in a bioactive liquid for 5-10 hours, and dried to obtain a finished product.

[0026] In detail, the melt copolymerization process is: lactic acid and glycolic acid are mixed, a catalyst is added, the mixture is reacted at 150-200° C. for 8-12 hours, and vacuum dried.

[0027] In detail, the mass of the catalyst is 0.1-0.4% of the mass of the mixture of lactic acid and glycolic acid, and the catalyst is SnCl 2 .

[0028] The repair material is degraded from high-molecular and macromolecular substances into small-molecular substances that do no harm to the body through the action of hydrolysis and enzymolysis. These small-molecular degradation products usually exist in the body itself, such as amino acids, carbon dioxide, water, etc. Finally, they are completely absorbed and excreted through the body's metabolism, without toxic side effects to the body, and can avoid the problem of related complications caused by the long-term retention of foreign matter in the body. The specific degradation process is: the surface of the degradable polymer material is adhered by microorganisms, and under the action of enzymes secreted by microorganisms, the polymer breaks into relatively small molecular fragments, and the microorganisms absorb or consume the fragments, which are finally metabolized to form water and carbon dioxide, etc.

[0029] The degradable polymer repair material of the present invention has special biological activity, good biocompatibility and biosafety, and also has excellent mechanical strength, chemical stability, biodegradability, can be used as sutures, and can also be used by weaving to form planar tissue. The planar tissue has high tensile strength, and the elastic recovery force and load distribution of each aspect are uniform and consistent, not easy to deform, can provide sufficient support and anti-bending particles, can effectively protect the internal organs from damage, and prevent abnormal breathing; it has low extensibility, the structural elasticity in the warp and weft directions is small, the structure is stable and uniform, and not easy to deform; it has a certain stiffness, is not easy to wrinkle, and the pore size is evenly distributed, which can provide a three-dimensional space for the growth, infiltration and migration of tissue cells. When it is degraded, it can allow the chest wall to grow and heal, so that the chest wall can play the role of protecting the internal organs again.

[0030] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0031] Example 1

[0032] A method for preparing a degradable polymer repair material comprises the following steps:

[0033] Raw materials: 5g polyanhydride, 1g calcium phosphate, 10g lactic acid, 0.5g polyethylene glycol, 10g glycolic acid, 3g bioactive liquid and 2g antimicrobial agent;

[0034] S1, dissolving polyethylene glycol in water, adding calcium phosphate and polyanhydride, stirring, aging for 3 days, and freeze-drying to obtain a first polymer monomer;

[0035] S2, mix lactic acid and glycolic acid, add catalyst SnCl 2 , SnCl 2 The mass of the mixture of lactic acid and glycolic acid is 0.2%, reacted at 180°C for 10 hours, and vacuum dried to obtain a second polymer monomer;

[0036] S3, mixing and melting the first polymerizable monomer and the second polymerizable monomer, adding an antibacterial agent, spinning, cooling and shaping, and obtaining a prefabricated material;

[0037] S4, soaking the prefabricated material in the bioactive liquid for 8 hours, drying, and obtaining a finished product.

[0038] In this embodiment, the bioactive liquid includes collagen and epidermal growth factor, and the mass ratio of the two is 1:3. The antibacterial agent is a mixture of berberine and curcumin, and the mass ratio of the two is 1:1.6.

[0039] Example 2

[0040] A method for preparing a degradable polymer repair material comprises the following steps:

[0041] Raw materials: 10 g polyanhydride, 0.5 g calcium phosphate, 5 g lactic acid, 0.8 g polyethylene glycol, 8 g glycolic acid, 4 g bioactive liquid and 1 g antimicrobial agent;

[0042] S1, dissolving polyethylene glycol in water, adding calcium phosphate and polyanhydride, stirring, aging for 2 days, and freeze-drying to obtain a first polymer monomer;

[0043] S2, mix lactic acid and glycolic acid, add catalyst SnCl 2 , SnCl 2 The mass of the mixture of lactic acid and glycolic acid is 0.2%, reacted at 160°C for 8h, and vacuum dried to obtain a second polymer monomer;

[0044] S3, mixing and melting the first polymerizable monomer and the second polymerizable monomer, adding an antibacterial agent, spinning, cooling and shaping, and obtaining a prefabricated material;

[0045] S4, soaking the prefabricated material in the bioactive liquid for 6 hours, drying, and obtaining a finished product.

[0046] In this embodiment, the bioactive liquid includes collagen and epidermal growth factor, and the mass ratio of the two is 1:2. The antibacterial agent is a mixture of berberine and curcumin, and the mass ratio of the two is 1:1.5.

[0047] Example 3

[0048] A method for preparing a degradable polymer repair material comprises the following steps:

[0049] Raw materials: 8g polyanhydride, 1g calcium phosphate, 8g lactic acid, 0.3g polyethylene glycol, 5g glycolic acid, 4g bioactive liquid and 3g antimicrobial agent;

[0050] S1, dissolving polyethylene glycol in water, adding calcium phosphate and polyanhydride, stirring, aging for 4 days, and freeze-drying to obtain a first polymer monomer;

[0051] S2, mix lactic acid and glycolic acid, add catalyst SnCl 2 , SnCl 2 The mass of the mixture of lactic acid and glycolic acid is 0.2%, reacted at 200°C for 10 hours, and vacuum dried to obtain a second polymer monomer;

[0052] S3, mixing and melting the first polymerizable monomer and the second polymerizable monomer, adding an antibacterial agent, spinning, cooling and shaping, and obtaining a prefabricated material;

[0053] S4, soaking the prefabricated material in the bioactive liquid for 8 hours, drying, and obtaining a finished product.

[0054] In this embodiment, the bioactive liquid includes collagen and epidermal growth factor, and the mass ratio of the two is 1:4. The antibacterial agent is a mixture of berberine and curcumin, and the mass ratio of the two is 1:1.8.

[0055] Example 4

[0056] A method for preparing a degradable polymer repair material comprises the following steps:

[0057] Raw materials: 4 g polyanhydride, 0.8 g calcium phosphate, 4 g lactic acid, 0.3 g polyethylene glycol, 6 g glycolic acid, 2 g bioactive liquid and 1 g antimicrobial agent;

[0058] S1, dissolving polyethylene glycol in water, adding calcium phosphate and polyanhydride, stirring, aging for 3 days, and freeze-drying to obtain a first polymer monomer;

[0059] S2, mix lactic acid and glycolic acid, add catalyst SnCl 2 , SnCl 2 The mass of the mixture of lactic acid and glycolic acid is 0.3%, reacted at 150°C for 8 hours, and vacuum dried to obtain a second polymer monomer;

[0060] S3, mixing and melting the first polymerizable monomer and the second polymerizable monomer, adding an antibacterial agent, spinning, cooling and shaping, and obtaining a prefabricated material;

[0061] S4, soaking the prefabricated material in the bioactive liquid for 5 hours, drying, and obtaining a finished product.

[0062] In this embodiment, the bioactive liquid includes collagen and epidermal growth factor, and the mass ratio of the two is 1:2. The antibacterial agent is a mixture of berberine and curcumin, and the mass ratio of the two is 1:1.5.

[0063] Test results

[0064] The repair materials prepared in Examples 1-4 were subjected to mechanical property testing. The repair materials of the same length were taken as samples. There was no significant difference in thickness between each sample. After each group of samples was stretched 4 times at different temperatures, the strength and elongation of the samples were tested. The results are as follows:

[0065] Table 1 Strength and elongation of samples after stretching 4 times at different temperatures

[0066]

[0067] According to Table 1, the repair materials prepared in Examples 1-4 have good tensile strength at 50° C. and good elongation at 70° C. This shows that the repair material of the present invention has good tensile strength at low temperatures and can have sufficient supporting force to stabilize the thorax and promote recovery.

[0068] The degradation performance of the repair materials prepared in Examples 1-4 was tested, and the results were as follows:

[0069] Table 2 Degradation time

[0070] Group Example 1 Example 2 Example 3 Example 4 Degradation time (days) 160 165 170 162

[0071] According to Table 2, the degradation time of the repair materials prepared in Examples 1-4 of the present invention is greater than three months, indicating that they can meet the requirements for repairing chest wall defects.

[0072] In summary, the degradable polymer repair material of the embodiment of the present invention, the polyanhydride has good fiber-forming properties and mechanical strength, and can form a porous first polymer monomer with a certain mechanical strength after cross-linking with calcium phosphate, which has cell compatibility, can enhance cell proliferation and adhesion, and can effectively promote the repair of chest wall defect tissue. The second polymer monomer is obtained after copolymerization of lactic acid and glycolic acid, which can enhance the ability of bone regeneration, and also has obvious antibacterial, bone conduction, bone induction and other properties, which can promote the recovery of the thorax. At the same time, its good relatively long-term mechanical properties in the human body can further improve the mechanical properties of the repair material. Polyethylene glycol has excellent gelation and degradability, good biocompatibility, non-toxicity and low immunogenicity. The combination of the first polymer monomer and the second polymer monomer can make the material have very good softness, crystallinity and degradability. Assisted by antibacterial agents, it can improve the protective effect on wounds, and assisted by biologically active liquids, it can supplement nutrients and promote cell reproduction, so as to further enhance the repair effect on chest wall defects and promote body recovery. The repair material is degraded from high-molecular and macromolecular substances into small-molecular substances that do no harm to the body through the action of hydrolysis and enzymolysis. These small-molecular degradation products usually exist in the body itself, such as amino acids, carbon dioxide, water, etc. Finally, they are completely absorbed and excreted through the body's metabolism, without toxic side effects to the body, and can avoid the problem of related complications caused by the long-term retention of foreign matter in the body. The specific degradation process is: the surface of the degradable polymer material is adhered by microorganisms, and under the action of enzymes secreted by microorganisms, the polymer breaks into relatively small molecular fragments, and the microorganisms absorb or consume the fragments, which are finally metabolized to form water and carbon dioxide, etc.

[0073] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0074] Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is therefore intended that all changes falling within the meaning and range of equivalent elements of the claims are included in the present invention.

Claims

1. A degradable polymer repair material, characterized in that: The raw materials include, by weight: 1-10 parts of polyanhydride, 0.5-2.5 parts of calcium phosphate, 1-10 parts of lactic acid, 0.1-1 parts of polyethylene glycol, 1-10 parts of glycolic acid, 1-5 parts of biologically active liquid and 1-5 parts of antibacterial agent; The preparation method of the degradable polymer repair material comprises the following steps: dissolving polyethylene glycol in water, adding calcium phosphate and polyanhydride, stirring, aging for 2-5 days, freeze-drying to obtain a first polymer monomer; melt copolymerizing lactic acid and glycolic acid to obtain a second polymer monomer; mixing and melting the first polymer monomer and the second polymer monomer, adding an antibacterial agent, spinning, cooling and shaping to obtain a prefabricated material, soaking the prefabricated material in a bioactive liquid, drying, and obtaining a finished product.

2. The degradable polymer repair material according to claim 1, characterized in that: The bioactive liquid includes collagen and epidermal growth factor, and the mass ratio of the two is 1:2-4.

3. The degradable polymer repair material according to claim 2, characterized in that: The antibacterial agent is a mixture of berberine and curcumin, and the mass ratio of the two is 1:1.5-1.

8.

4. The degradable polymer repair material according to claim 1, characterized in that: The melt copolymerization process is as follows: lactic acid and glycolic acid are mixed, a catalyst is added, the mixture is reacted at 150-200° C. for 8-12 hours, and vacuum dried.

5. The degradable polymer repair material according to claim 4, characterized in that: The mass of the catalyst is 0.1-0.4% of the mass of the mixture of lactic acid and glycolic acid, and the catalyst is SnCl2.

6. The degradable polymer repair material according to claim 1, characterized in that: When soaking, the soaking time is 5-10h.

Citation Information

Patent Citations

  • Absorbable active tissue matter for repairing hard tissue and its prepn

    CN1403166A